2016
DOI: 10.1097/prs.0000000000001865
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide versus Saline Tissue Expanders

Abstract: The authors believe that carbon dioxide-based devices may play a significant role in the future of implant-based breast reconstruction, and may be widely applicable to other areas of plastic surgery that also involve tissue expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In autologous fat grafting, fat is harvested, processed, and transplanted to different parts of the body. It has proven a valuable treatment regimen in patients suffering from multiply determined chronic pain [1314]. In previous studies, a significant reduction of pain was reported after treatment with AFG for patients with post-mastectomy pain syndrome [67] or painful scars with a mean follow-up ranging from 10 to 14 months [5678].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In autologous fat grafting, fat is harvested, processed, and transplanted to different parts of the body. It has proven a valuable treatment regimen in patients suffering from multiply determined chronic pain [1314]. In previous studies, a significant reduction of pain was reported after treatment with AFG for patients with post-mastectomy pain syndrome [67] or painful scars with a mean follow-up ranging from 10 to 14 months [5678].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, a significant reduction of pain was reported after treatment with AFG for patients with post-mastectomy pain syndrome [67] or painful scars with a mean follow-up ranging from 10 to 14 months [5678]. The mesenchymal cells of the fat graft are thought to give prolonged analgesia by changing the microenvironment and the secretion of substances [671314]. In the literature, a resorption rate of 17% to 82% of the injected fat is reported [15], which could explain why repeated treatment is required.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receive weekly injections, over the course of 6-8 weeks. 7,8 The AeroForm TE (AirXpanders, Palo Alto, CA, USA) consists of a silicon shell containing a stainless steel reservoir of compressed CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…If radiation is indicated, the patient is typically simulated and treated after expansion is complete. 8,9 Tissue expanders pose particular challenges in a radiation oncology setting. The high-density metallic components of both types of TE cause artifacts in treatment planning CT images.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the proven regenerative potential expressed by its stromal vascular fraction, has been applied for the treatment of scars, scar-related conditions and burns. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%